Hubungan Antara Kualitas Pelayanan Kefarmasian Pasien Rawat Jalan Dengan Tingkat Kepuasan di Puskesmas X - Indrasari, Ferika; Riyantara, Rahma Widya; Maryeta, Eleonora; Suwarni, Sri (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Pharmaceutical service is a responsible service directly to patients related to pharmaceutical preparations with the aim of achieving is to improve patient life quality. Service quality always be complained by patient when get treatment in the Public Health. Worse service, unfriendly, slow service is a factor that affects the quality of service. The level of satisfaction is a comparison function between performance obtained and expectations. When performance is below expectations, the customer will disappointed and vice versa. This research to know the correlation the quality of pharmacy services with outpatient satisfication in the Purwodadi II Public Health. This research used an analytical observational method with a cross sectional design with a sample technique using purposive sampling technique. This data is main data by filling out questionnaires of patients that seeking treatment in the Purwodadi II Health. The process of data analysis in this study are 1. Editing 2. Coding 3. Scoring 4. Tabulating. From the results of this study, it was found that there was a significant relationship between service quality dimensions of reliability, responsiveness, assurance, empathy, and tangibels outpatient pharmacy with the level of satisfaction at Puskesmas Purwodadi II with a p-value of reliability dimension 0.001, responsiveness 0.002, assurance 0.001, empathy 0.000, and tangibels 0.000(p-value<0,05).